Art Pedagogy Is An Integral Part Of The Educational Process - Babanazarova Maftuna Nazarbekovna (Genius Journals, 2024)
This article represents an in-depth analysis and significance of the use of art pedagogy in primary education. The authors substantiate the indispensability of art integration into the educational process of primary school, emphasizing that art pedagogy not only complements traditional teaching methods, but also plays a key role in the formation of fundamental skills and the development of creative thinking in primary schoolchildren. The article examines in detail various aspects of art pedagogy, adapted to the characteristics of primary education. The article examines the significance of the use of art pedagogy in primary education in Uzbekistan. The authors discuss the impact of creative learning on the development of creative thinking, personal qualities, and emotional intelligence in primary schoolchildren. Emphasis is placed on the use of artistic forms to build social skills and integration with other subjects. The article provides an overview of current trends in art pedagogy in Uzbek schools, and also discusses the prospects for the development of this approach in the context of the country's educational reforms. Ultimately, the abstract highlights the importance of incorporating creative arts into early learning, building a bridge to deeper and more sustainable educational experiences for future generations
Keywords: art pedagogy; primary education; method; style